Human adenovirus infection induces pulmonary inflammatory damage by triggering noncanonical inflammasomes activation and macrophage pyroptosis - Li, Lexi; Fan, Huifeng; Zhou, Jinyu; Xu, Xuehua; Yang, Diyuan; Wu, Minhao; Cao, Can; Lu, Gen (Frontiers in Immunology, 2023)
Human adenovirus (HAdV) is a common respiratory virus, which can lead to severe pneumonia in children and immunocompromised persons, but the regulatory mechanism of HAdV-induced pulmonary inflammatory damage remains unclear. Bioinformatics analysis showed that inflammasome-related genes, including caspase-4 and caspase-5, were enriched in adenovirus pneumonia. Moreover, caspase-4 and caspase-5 expression levels were significantly increased in the cells isolated from peripheral blood and broncho-alveolar lavage fluid (BALF) of pediatric patients with adenovirus pneumonia, and positively correlated with clinical parameters of inflammatory damage. In vitro experiments revealed that HAdV infection promoted caspase-4/5 expression, activation and pyroptosis in differentiated THP-1 (dTHP-1) human macrophages via NF-κB, rather than STING signaling pathway. Interestingly, silencing of caspase-4 and caspase-5 in dTHP-1 cells suppressed HAdV-induced noncanonical inflammasome activation and macrophage pyroptosis, and dramatically decreased the HAdV titer in cell supernatants, by influencing virus release rather than other stages of virus life cycle. In conclusion, our study demonstrated that HAdV infection induced macrophage pyroptosis by triggering noncanonical inflammasome activation via a NF-B-dependent manner, which may explore new perspectives on the pathogenesis of HAdV-induced inflammatory damage, and therefore provide potential antiviral strategy and biomarker for predicting the severity of adenovirus pneumonia.